(untitled) (Salam International Academic Journal, 2022)
The article titled: "Reflection of Concepts of the Holy Qur’an in the Poems of Allama Iqbal Lahori" includes the following topics: In the first topic, the issues of belief and monotheism are discussed. First of all, the greatness of Almighty Allah, the creator of the universe and the attributes of Almighty Allah are discussed. The Poet Allama Iqbal has described the signs of Allah’s power and greatness in a beautiful way. Next, he has explained the source of honor and humiliation, which is from Allah, and emphasized that the Lord of the universe is closer to His servants than jugular vein. The second topic elaborated the position of the Holy Quran and its main features. The third topic is allotted to the mission, attributes and high position of the Prophet of Mohammad (PBUH). In this topic, it is also mentioned that Islam is the last divine religion on earth, and Prophet Muhammad’s (PBUH) mission is the last heavenly mission. In the fourth and fifth topics, he precisely explained the concept of belief in the Hereafter and its profound effects on the lives of servants, and also described the concept of belief in the fate of good and evil. In general, the first topic, which constitutes Allama Iqbal’s beliefs, is the most important part of the article. In the second topic of the article, the ethical concepts and human habits are elaborated. The major moral issues that the Holy Qur’an pays attention to are: brotherhood and peace-seeking, moral deviation of religious people from the path of Islam, expressing regret for wrong deeds and self-blame, sincerity and solitude that can be considered the secret to success. Human’s position in the universe is another issue that has been discussed from different aspects, such as the equality of all humans in creation, the expression of human’s natural and ethical attributes for which angels were ordered to prostrate to Adam. The fourth topic of this article has been allocated to divine commands on good deeds, such as encouraging people to pray five times a day and say midnight prayers which strengthen connection between a servant and Allah, supplications, fleeing to Allah and seeking closeness to Allah, thinking about the phenomena of power of Allah in creatures and thinking about the dire destiny of the oppressors, accepting the burden of Islam by humans and paying attention to the Islamic law and adhering to it. In the fifth topic, social issues, such as insisting on unity and warning against division, the position of women in human society from the perspective of Islamic teachings, and that women complement men’s lives, have been studied. In the sixth topic, titled "Dawat (Invitation to Islam), mujaahadah (striving for a religious cause) and Revolution", we have discussed the following issues: Calling people for comprehensive change and revolution, describing the great effects of religious beliefs on the human soul and psyche and proving that the Islamic Ummah is a just and moderate Ummah. In addition, we have discussed that Iqbal calls others to follow the Prophet of Islam, no matter how illiterate he or she is, and calls Muslims to true jihad and self-sacrifice to fulfill their ultimate goals.